Unilateral Application of Cathodal tDCS Reduces Transcallosal Inhibition and Improves Visual Acuity in Amblyopic Patients - Bocci, Tommaso; Nasini, Francesco; Caleo, Matteo; Restani, Laura; Barloscio, Davide; Ardolino, Gianluca; Priori, Alberto; Maffei, Lamberto; Nardi, Marco; Sartucci, Ferdinando (Frontiers in Behavioral Neuroscience, 2018)
Objective: Amblyopia is a neurodevelopmental disorder characterized by visual acuity and contrast sensitivity loss, refractory to pharmacological and optical treatments in adulthood. In animals, the corpus callosum (CC) contributes to suppression of visual responses of the amblyopic eye. To investigate the role of interhemispheric pathways in amblyopic patients, we studied the response of the visual cortex to transcranial Direct Current Stimulation (tDCS) applied over the primary visual area (V1) contralateral to the “lazy eye”. Methods: Visual acuity (logMAR) was assessed before (T0), immediately after (T1) and 60’ following the application of cathodal tDCS (2.0 mA, 20’) in twelve amblyopic patients. At each time point, Visual Evoked Potentials (VEPs) triggered by grating stimuli of different contrasts (K90%, K20%) were recorded in both hemispheres and compared to those obtained in ten healthy volunteers. Results: Cathodal tDCS improved visual acuity respect to baseline (p < 0.0001), whereas sham polarization had no significant effect. At T1, tDCS induced an inhibitory effect on VEPs amplitudes at all contrasts in the targeted side and a facilitation of responses in the hemisphere ipsilateral to the amblyopic eye; compared with controls, the facilitation persisted at T2 for high contrasts (K90%; Holm–Sidak post-hoc method, p < 0.001), while the stimulated hemisphere recovered more quickly from inhibition (Holm–Sidak post-hoc method, p < 0.001). Conclusions: tDCS is a promising treatment for amblyopia in adults. The rapid recovery of excitability and the concurrent transcallosal disinhibition following perturbation of cortical activity may support a critical role of interhemispheric balance in the pathophysiology of amblyopia.